Prognostic significance of combined score of fibrinogen and neutrophil-lymphocyte ratio for functional outcome in patients with aneurysmal subarachnoid hemorrhage - Hou, Yuyang; Li, Hua; Yang, Hongkuan; Chen, Rudong; Yu, Jiasheng (Frontiers in Neurology, 2022)
Abstract: Objective: To explore the relationship between fibrinogen and neutrophil to lymphocyte ratio (F-NLR) score and functional outcome after aneurysmal subarachnoid hemorrhage (aSAH). Method: A retrospective study was conducted that involved all consecutive aSAH patients admitted to our institution from March 2018 to October 2021. Factors including demographics, comorbidities, clinical characteristics, neuroradiological data, as well as laboratory parameters, were collected from institutional databases. All patients achieved neurological assessment using the modified Rankin Scale (mRS) score 3 months after discharge to clarify the functional outcomes. The results were classified as favorable (mRS score 0–2) and unfavorable (mRS score 3–6). Univariate and multivariate analysis were performed to identify the relevant factors between inflammatory markers and functional outcomes after aSAH. Subsequently, receiver operating characteristic (ROC) curve analysis was conducted to evaluate the predicting performance of variables. A propensity score match (PSM) was performed to correct imbalances in patient baseline characteristics. Results: Finally, 256 patients with aSAH were included in study cohort. A total of 94 (36.7%) patients had an unfavorable outcome. F-NLR score was 0 (IQR 0-1) and 1 (IQR 1-2) in patients with favorable and unfavorable outcome, respectively (p < 0.001). After adjustment, the F-NLR score on admission remained significantly associated with unfavorable outcome in patients with aSAH. In the multivariate analysis, F-NLR score was regarded as an independent risk factor of unfavorable outcomes (OR 3.113 95% CI 1.755-5.523, p < 0.001). In ROC analysis, the optimal cut-off value of F-NLR score was 0.5 point. Two cohorts (n = 86 in each group) obtained from PSM with low F-NLR score (0 point) and high F-NLR score (1-2 point) were used for analysis. A significantly higher unfavorable functional outcome rate was observed in patients with high F-NLR score (33.7% vs 9.3%, p < 0.001). The area under the curve (AUC) of F-NLR score before and after propensity score match was 0.767 and 0.712, respectively. Conclusions: F-NLR score was an independent risk parameter associated with unfavorable functional outcome at 3 months after aSAH. Higher F-NLR score predicts the occurrence of poor functional outcome.